The Contribution of Women in Religious Preaching in the Middle East - Arif, Abid Faturrahman; Nurwahidin, Nurwahidin (Universitas Muhammadiyah Gorontalo, 2024)
This article is based by the domination of the role of men over women in Middle Eastern society, whereas when viewed from the religious perspective of the majority of Middle Eastern society, namely Islam, women is highly respected and have a special position in society. This is due to the pre-Islamic culture and perceptions that undermine women in their social status, so that women are only objects of entertainment, household and sexuality without being permitted to massive public activities. This situation lasted for some time, until finally a modern religious and social-based movement that fought for women's rights emerged. According to the theory of liberal feminism, women should get the same rights as men, while maintaining the natural differences that exist between the two. A woman cannot be confined at home and taking care of her family, but she has the right to socialize and appear in public. Although discrimination against women continues, in fact there are women who have recorded their role of preaching to society. If all this time the preachers were generally male, then history records that there were female preachers who were influential in the religious life of Middle Eastern society. The research method I use is descriptive-analysis based on literature review. Based on the study that I convey in this article, the contribution of women in religious preaching in the Middle East is a reality that should be appreciated amidst globalization and modernization, even though the culture of patriarchy and women's subordination has not completely disappeared and has become a hereditary culture of Middle Eastern society.